Revisionist strategies in the English-language feminist critics and women’s literature in the second half of the XX century and at the beginning of the XXI century - Yankuta, Hanna V. (Journal of the Belarusian State University. Philology, 2019)
The article characterizes the issues of feminist literary studies in the 1970s and 1980s, the main purpose of which was rethinking of the literary canon through the prism of female experience, and revision as a key method of feminist criticism (the history of the concept’s appearance, its meaning and interpretation by different researchers). It reveals the significance of self-revision for feminist literary criticism, which allows to includ the experience of all women groups in the research context. It analyses revision as a creative strategy used by women writers in the second half of the XX and at the beginning of the XXI century: the revision of the language and style that resulted in the creating of the «écriture feminine» conception, the revision of myths and classical literary works, which leads to the deconstruction of traditional plots and to the coming to the fore of the female characters. It states that the revision of the genre system is manifested through the transformation of such elements of genre form and genre content as the thematic and problematic issues, the subject arranging of the literary universe and the system of images in the work, which influences new genre modifications.